A Bioarchaeological Study of African American Health and Mortality in the Post-Emancipation U.S. South. Issue 4 (October 2020) - Franklin, Maria; Wilson, Samuel M.
Abstract : After emancipation, most African Americans remained tethered to agricultural economies, while others migrated to cities seeking better opportunities. Although bioarchaeologists have made significant interventions in researching people of African descent, there are relatively few published comparative studies that address their morbidity and mortality after slavery. This study compares the bioarchaeological evidence for rural and urban southern United States populations to address disparities in health and longevity. It considers the biological effects of racism, including the health impacts of poverty, disease, and malnourishment. Although historians and demographers argue that urban life was especially detrimental to health, the results of this research suggest greater complexity in African American well-being. Whereas urban adults had higher midlife mortality and reduced longevity compared to their rural counterparts, both rural and urban children experienced poor health. Rural child mortality and morbidity varied significantly, suggesting differences in diet and disease exposure across rural communities. With regard to gender, rural and urban women died at younger ages than men. This disparity in mortality is partly attributed to black women's working and reproductive lives within the context of racism and gender inequality.